THE EFFECTIVENESS OF DIGITAL MARKETING TRAINING IN INCREASING SALES OF MSME PRODUCTS IN LEMAHPUTRO VILLAGE - Damayanti, Novia Rahma; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of digital marketing training in improving the marketing of Micro, Small, and Medium Enterprises (MSMEs) products in Lemahputro Village, Sidoarjo. Method: The research uses a qualitative descriptive approach by applying Campbell's effectiveness theory through four indicators, namely program success, target accuracy, program satisfaction, and overall goal achievement. Data were collected through interviews, observations, and documentation, and reinforced with secondary data from government reports and village profiles. Results: The results showed that digital marketing training was considered effective in all four indicators: program success was supported by the active involvement of the village and regional governments, target accuracy was achieved through the selection of relevant participants, participant satisfaction increased thanks to interactive methods and adequate facilities, and overall objectives were proven through increased MSME turnover and the implementation of digital marketing practices. This training not only changed the marketing behavior of MSME actors but also contributed to village economic growth. Novelty: The novelty of this research lies in its emphasis on the important role of the village government as a determining factor in the success of MSME digital transformation, making synergy between MSMEs and the government the key to sustainable village economic development.